INNOVATIONS AND THEIR ROLE IN ORGANIZATION OF ENTERPRISE WORK - Rimma P. Kazakova; Galina I. Bolkina (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article discusses different views on the idea of innovations. It identifies the aims and objectives of innovation management, shows its orientation to changes in the field of planning, organization, management, control and analysis of innovation processes at the enterprise in strategic and operational aspect. Special attention is paid to practical experience of organizing innovation activity at Zhukovskiy plant of technological equipment. The authors give recommendations on intensifying labour motivation on the basis of material incentives for authors of innovative projects, timing of bonus payment was fixed. It was proposed to take into account the contribution of each division to profit growth, which was attained at the expense of the innovative product.